Carbon dioxide sequestration by algae in pome medium - Nor Shahida, Hamdan (2014)
Carbon dioxide (CO2) has been identified as one of the primary greenhouse gases (GHG) in the atmosphere. Carbon dioxide emissions have increased by about 35% since 1990 and cause the global warming. In Malaysia, this problem is due to the rapid growth of palm oil industries. A lot of carbon dioxide is emitted in producing crude palm kernel oil. Besides, palm oil mill effluent (POME) is the waste discharged by the palm oil industries with high biochemical oxygen demand (BOD), which has created serious water pollution in Malaysia, but it contains micronutrient need for microalgae growth. CO2 emission can be reduced through CO2 sequestration by photoautotrophic algae through photosynthesis. In this study, microalgae (Chlorella sp.) was cultured in POME medium in conical flasks and the interaction effect of light intensity and CO2 concentration in the sparged mixture of air and CO2 on algae growth (expressed as cell dry weight and specific growth rate) were identified. Then the results obtained from this experiment were analyzed with 2-level factorial design by using Design Expert 6.0.8 Software. In this experiment, the light intensity was supplied by fluorescent lamps at 2,000-12,000 lux. Meanwhile, the microalgae culture was sparged by 5 L/min of air mixture with CO2 concentration (2-10% v/v). From this study, it was found that the increasing of light intensity and the increasing of CO2 concentration gives the highest cell dry weight. At low light intensity, cell dry weight decreased even the CO2 increased. The interaction between light intensity and CO2 concentration in cell dry weight production was insignificant. In response to specific growth rate of Chlorella sp., at low CO2 concentration, increasing light intensity did not affect the specific growth rate. On the other hand, when CO2 concentration was high, increasing light intensity would reduce the specific growth rate of Chlorella sp. Both factors (light intensity and CO2 concentration) were identified as the significant in effecting specific growth rate of Chlorella sp. As conclusion, since the CO2 sequestration was measured based on the cell dry weight produce, light intensity was the significant factor for CO2 sequestration by Chlorella sp. in POME medium. Nevertheless, too high a light intensity would cause photo-inhibition and reduced the growth rate of Chlorella sp. which in turn slows down the process of CO2 sequestration